Pengaruh Omnichannel Marketing dan Product Assortment terhadap Minat Beli dan Keputusan Pembelian Konsumen UMKM FNB di Pandaan - Lestari, Nisya Wahyu; Huda, Miftahul (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
The Indonesian business world is currently developing very quickly, which is causing business competition to become increasingly fierce. This is also felt by food and beverage business actors.This research aims to determine the influence of Omni Channel Marketing and Product Assortment on Purchase Interest and Purchase Decisions of FNB MSME Consumers in Pandaan District. The type of research used in this research is explanatory research with a quantitative approach. The sampling technique was carried out using Non Probability Sampling with purposive sampling technique. The number of samples in this study was 116 respondents. Data collection was carried out by distributing questionnaires directly to FNB MSME customers in Pandaan who were the objects of research. The data obtained in this research was analyzed using Structural Equation Modeling (SEM) analysis techniques based on the PLS (Partial Least Square) variant with the help of SmartPLS 4.0 software. Testing of this research model was carried out using outer model (measurement model) and inner model (structural model) tests. The results of this research show that the Omni Channel Marketing variable has a positive and significant effect on Purchase Interest, Product Assortment has a positive and significant influence on Purchase Interest, Omni Channel Marketing has a positive and significant influence on Purchase Decisions, Product Assortment has a positive and significant influence on Purchase Decisions, Purchase Interest positive and significant effect on Purchasing Decisions.